ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIASAAN MENGEMUDI TIDAK AMAN PADA SOPIR ANGKOT DAERAH TEMBALANG KOTA SEMARANG - Dian Putri Nastiti; Baju Widjasena; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Safety driving is safe driving behaviors that can help to avoid traffic problems as well as basic training further driving more attention to safety for drivers and passengers. In Indonesia in 2011 there were 108 696 accidents, an increase of almost 70% from 2010, amounting to 66 488 road accidents. Tembalang transportation drivers in the area are likely to have unsafe driving habits, such as not using a safety belt, violating rules and traffic signs as well as stop and brake suddenly. Transportation drivers driving habits that are unsafe can lead to traffic accidents and the impact of traffic accidents not only have implications for public transportation drivers but also for the impact on passengers and other motorists. The purpose of this study was to determine the factors that influence unsafe driving habits on public transportation drivers in the area Tembalang. The research is a qualitative descriptive analysis method is done by in-depth interviews and field observations. Subjects of this study is that the main informant transportation drivers Tembalang area, while the informant triangulation consist of passengers, other motorists, owner transportation and the head of traffic police. Based on the research results, unsafe driving habits on public transportation drivers Tembalang Semarang area such as not using safety belt while driving, do not comply with regulations and traffic signs and stop or brake suddenly. Unsafe driving habits influenced by several factors, thee are attitude and professionalism of public transportation drivers, motivation, condition of the vehicle, minivan owner, colleague, organization, training driving safety, the absence of a stop or special stops for public transportation and supervision of the police